THE CORRELATION BETWEEN THE ROLE OF PARENTS AND THE OCCURRENCE OF PREGNANT ADOLESCENTS OUTSIDE OF MARRIAGE IN THE WORKING AREA OF THE HAMAMPARAN PERAK HEALTH CENTER, HAMPARAN PERAK SUB-DISTRICT, DELI SERDANG REGENCY YEAR 2023 - Eva Ratna Dewi; Lidya Natalia Br. Sinuhaji; Ingka Kristina Pangaribuan; Markus Doddy Simanjuntak; Sulina; Ingati Nduru (International Journal of Midwifery Research, 2023)
Cases of juvenile delinquency are increasing and attracting attention. The problem is increasing and worrying. A lot of news in various media raised about the problems of adolescents. One of them is getting pregnant out of wedlock. This study aims to determine and analyze the relationship between the role of parents and the incidence of pregnant teenagers out of wedlock in the working area of the Hamparan Perak Health Center, Hamparan Perak District, Deli Serdang Regency in 2023. The type of research was used is descriptive research. The population in this study were all teenagers who were pregnant out of wedlock in the Work Area of the Hamparan Perak Health Center, as many as 50 respondents. The number of samples used was 50 respondents with the total sampling technique. Data analysis technique using chi-square. Based on the results of the chi square, it was found that there was a significant influence between knowledge of pregnancy out of wedlock with a p-Value of 0.001 with a coefficient of <0.05. There is a significant relationship between the role of parents and pregnancies outside of marriage in the work area of the Hamparan Perak Health Center, Hamparan Perak District, Deli Serdang Regency in 2022. It is recommended for all adolescents to be able to avoid promiscuity, because promiscuity can result in pregnancies outside of marriage.